2018
DOI: 10.1016/j.phymed.2018.03.053
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized liposomes and phytosomes loading Annona muricata L. aqueous extract: Potential nanoshuttles for brain-delivery of phenolic compounds

Abstract: Overall, phytosome formulations registered the best performance in terms of binding efficiency, enzyme inhibition and scavenging activity, thus representing a promising multipotent phenolic-rich nanoshuttle for future in vivo depression treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 64 publications
(83 reference statements)
0
29
0
Order By: Relevance
“…The sustained release pattern of CEP-1:3 compared with that of CEP-1:2 may be partly explained by the formation of a relatively stable complex. Mancini et al [37] compared the release characteristics of an Annona muricata extract-loaded phytosome and liposomes. They concluded that both nano-formulations retained their antioxidant activity.…”
Section: Resultsmentioning
confidence: 99%
“…The sustained release pattern of CEP-1:3 compared with that of CEP-1:2 may be partly explained by the formation of a relatively stable complex. Mancini et al [37] compared the release characteristics of an Annona muricata extract-loaded phytosome and liposomes. They concluded that both nano-formulations retained their antioxidant activity.…”
Section: Resultsmentioning
confidence: 99%
“…Annona muricata aqueous extract contains a large amount of bioactive phenols, which are found to regulate monoamine oxidase, a key brain enzyme in major depressive disorders. Aqueous extract of A. muricata was encapsulated in liposome for protecting the phenolics from gastro‐intestinal degradation and improved permeability across blood–brain barrier, thus retaining its bioactivities (Mancini et al., 2018). Health benefits of green tea rely on the abundance and types of bioactive polyphenols.…”
Section: Applications Of Liposomesmentioning
confidence: 99%
“…[14][15][16] A few researchers have reported the successful loading of AME extracts into drug delivery carriers to potentiate their cytotoxic effects through their sustained release to the target cells. [17][18][19] For instance, Aruan et al 17 incorporated AME leaf extracts into electrospun polyvinyl alcohol nanofiber scaffolds and demonstrated the cytotoxic effects of the released extracts on the growth of Staphylococcus aureus. Similar effects were exhibited by AME extracts loaded in liposomes and phytosmes 18 and freeze-dried matices.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] For instance, Aruan et al 17 incorporated AME leaf extracts into electrospun polyvinyl alcohol nanofiber scaffolds and demonstrated the cytotoxic effects of the released extracts on the growth of Staphylococcus aureus. Similar effects were exhibited by AME extracts loaded in liposomes and phytosmes 18 and freeze-dried matices. 19 However, these studies did not report on the release profiles and release kinetics of AME from the drug carriers, which are important for optimizing the drug delivery systems to facilitate the localized delivery of AME at desirable doses over longer durations to cancer cells.…”
Section: Introductionmentioning
confidence: 99%